2021
DOI: 10.3390/ijerph18168482
|View full text |Cite
|
Sign up to set email alerts
|

Trend Analysis of Patient Safety Incidents and Their Associated Factors in Korea Using National Patient Safety Report Data (2017~2019)

Abstract: This study analyzed trends in patient safety incidents (PSIs) and the factors associated with the PSIs by analyzing 2017–2019 Patient Safety Report data in Korea. We extracted 2940 records in 2017, 5889 in 2018, and 7386 in 2019, from hospitals with more than 200 beds, and used all 16,215 cases for analysis. SPSS 25.0 was used for a multi-nominal logistic regression analysis. The PSI trend analysis, the standardized Jonckheere–Terpstra test was significant. On analyzing the probability of adverse events based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 29 publications
(39 reference statements)
0
4
0
Order By: Relevance
“…In this study, it was found that a majority of the participants had experienced patient safety incidents, with falls being the most common type, consistent with the types of patient safety incidents reported by the Korean Institute for Healthcare Accreditation [15,16]. Therefore, guidelines and education for fall prevention considering the age and types of diseases of patients are necessary.…”
Section: Discussionsupporting
confidence: 79%
“…In this study, it was found that a majority of the participants had experienced patient safety incidents, with falls being the most common type, consistent with the types of patient safety incidents reported by the Korean Institute for Healthcare Accreditation [15,16]. Therefore, guidelines and education for fall prevention considering the age and types of diseases of patients are necessary.…”
Section: Discussionsupporting
confidence: 79%
“…This study showed that the percentages of the duration of nursing activities were scheduled medication (23.7%), documenting nursing care (21.2%), monitoring and measurements in patient surveillance (12.5%), and handover (12.5%). In a previous study, nursing activities were reported as follows: 24.6% for record keeping, 24.0% for handover, 13.9% for medication administration, 8.9% for measurements (e.g., vital signs), and 5.3% for communication 28 . In this study, scheduled medication included the process of preparing and collecting medications from the pharmacy, reclassifying drugs, and recording the time on the administration card for each patient before administering medication.…”
Section: Discussionmentioning
confidence: 99%
“…The 2018 Patient Safety Statistical Yearbook reports that 28.1% of patient safety accidents are caused by dosing errors, doubling from 1,075 cases in 2017 to 2,602 cases in 2018. Scheduled medication has an important impact on symptom management and patient safety 28 , 29 . Therefore, nurses spend a lot of time administering medications and monitoring patients to reduce medication errors.…”
Section: Discussionmentioning
confidence: 99%
“…Some researchers also say that elderly patients are three times more likely to fall. Patient Safety Incident Reports to improve strategy, monitoring, and prevention, and reduce unwanted events (Shin & Won, 2021).…”
Section: Introductionmentioning
confidence: 99%